2014
DOI: 10.1097/pec.0000000000000298
|View full text |Cite
|
Sign up to set email alerts
|

Imaging, Clearance, and Controversies in Pediatric Cervical Spine Trauma

Abstract: Diagnosing cervical spine injury in children can be difficult because the clinical examination can be unreliable, and evidence-based consensus guidelines for cervical spine injury evaluation in children have not been established. However, the consequences of cervical spine injuries are significant. Therefore, practitioners should understand common patterns of cervical spine injury in children, the evidence and indications for cervical spine imaging, and which imaging modalities to use. Herein, we review the ep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 64 publications
1
15
0
Order By: Relevance
“…Children under 9 years of age have cervical spines that differ from their older peers in that the fulcrum of motion of their cervical spine occurs at C2-C3, making injury of the upper cervical spine much more common [16]. Of the three patients under the age of nine with CSI in our study, all three were found to have upper cervical spine injury (C3 and above), as is expected in this age group.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…Children under 9 years of age have cervical spines that differ from their older peers in that the fulcrum of motion of their cervical spine occurs at C2-C3, making injury of the upper cervical spine much more common [16]. Of the three patients under the age of nine with CSI in our study, all three were found to have upper cervical spine injury (C3 and above), as is expected in this age group.…”
Section: Discussionsupporting
confidence: 59%
“…Of the 41 patients in the 9-18 age group, 30 patients (73 %) had injury either solely in the lower cervical spine or a combination of lower and upper cervical spine injury. This pattern of injury in the older pediatric group reflects their matured cervical spine, which has a fulcrum of motion at the C5-C6 level [16].…”
Section: Discussionmentioning
confidence: 90%
“…In adults, the National Emergency X-Radiography Utilization Study (NEXUS) criteria are well established. 3,[9][10][11]26,27 Garton and Hammer 28 found a remarkably lower sensitivity for the NEXUS criteria of 85% among children under the age of 9 years, and because of this, the Congress of Neurological Surgeons guidelines recommend application of the NEXUS decision instrument only in children over the age of 9 years. At least 1 positive item of the NEXUS criteria could be found in the 30 pediatric patients with a confirmed cervical spine injury in this study.…”
Section: Diagnosis and Initial Therapeutic Managementmentioning
confidence: 99%
“…In 603 low-risk patients (absence of any of the NEXUS criteria) no spinal injury was detected. 3,[7][8][9][10][30][31][32] The lateral view provides the highest sensitivity of up to 93% depending on patient age. 11 A major limitation of this study is that only 2.8% of the included patients were under the age of 2, which is the most crucial age group.…”
Section: Diagnosis and Initial Therapeutic Managementmentioning
confidence: 99%
See 1 more Smart Citation